Perancangan Dinding Pemecah Pada Mesin Pengupas Kulit Kopi Kering - Muzni Sahar; Muhammad Al Dhaffa; Amnur Akhyan (Jurnal Elektro dan Mesin Terapan, 2020)
Coffee is a beverage that is relatively favored by the people of Indonesia because of its taste and aroma. Takengon, Central Aceh district is one of the regions producing coffee beans in Indonesia. Many of the coffees we drink today are the result of coffee plantations originating from there. But many do not know that the process of making coffee drinks is not so easy, especially during the process of stripping the skin on coffee beans. The process of stripping the coffee husk is carried out by the community usually by turning the mill manually which is rotated by hand. Thus came the idea to make a Coffee Skin Peeling Machine Using Two Knives that can simplify the process of stripping the coffee skin efficiently and simply. This machine has 2 parts that can facilitate the stripping process, namely the rectifier shaft and paring knife. This machine can separate the results of stripping between beans and coffee mechanically and the best stripping percentage during the stripping process is 83% with an error percentage of 17 %.